The degraded contingency test fails to detect habit induction in humans - Sara Molinero; Pablo Martínez-López; Joaquín Morís; María J. Quintero; Pedro L. Cobos; Francisco J. López; David Luque (PLoS ONE, 2025)
In experimental psychology and behavioral neuroscience, habits are considered stimulus-response (S-R) associations formed through extended reward training. Accordingly, habits are assessed using one of two tests: 1) Outcome devaluation, in which the value of the outcome (reward) is reduced, making it less desirable, and 2) Contingency degradation, in which the response-outcome association is reversed so that responding prevents the delivery of a reward. If a behavior is controlled by S-R links, then it should remain mostly insensitive by these two manipulations. Animal research using the outcome devaluation test has shown that initially goal-directed actions can become habitual after extended operant training. However, replicating this transition in human research has proven challenging, representing a significant problem for translational research. Notably, the contingency degradation test has rarely been used in human research. In this study, we aimed to demonstrate a shift from goal-directed to habitual control through three pre-registered experiments. Participants were trained in two S-R-O (stimulus-response-outcome) mappings for three days, with one condition (the ‘overtrained’) occurring four times more frequently than the other (‘standard’). Importantly, we assessed the habitualization of both responses by using a degraded contingency test. Overall, we found no evidence of an overtraining effect — that is, the ‘overtrained’ condition did not lead to increased habitual responding. We discuss the theoretical and applied implications of these findings and explore further directions for studying habitual behavior.